MANAJAMEN PENGELOLAAN SUMBER DAYA MANUSIA TENAGA PENDAMPING PROFESIONAL DI PROVINSI NTB - Rosmiati; Titin Windiasari; Mayasni, Yayuk; Septiana, Rini (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2024)
Law No. 14 of 2014 concerning Villages article 12 Chapter II states that Village Assistants carry out the task of assisting Villages by assisting Villages in planning, implementing and monitoring Village development and empowering Village communities, accompanying Villages. The importance of the role of village assistants in overseeing the implementation of village law is that the Ministry of Villages carries out the management of Professional Assistance Personnel in human resource management in West Nusa Tenggara Province to realize organizational goals effectively and efficiently. This research aims to find out comprehensively about managing human resources in village assistants according to experts, which is compared with the regulations regarding the management of village assistants issued by the ministry of villages, disadvantaged areas and transmigration. The research method used is a descriptive method with a qualitative approach with a literature study type of research. The results of the research found firstly, that the Manjamen TPP management of village assistants in West Nusa Tenggara was carried out directly by the Ministry of Villages, Disadvantaged Areas and Transmigration which was regulated through a decree from the Minister of Villages and carried out by BPSDM. Second, the management of village funds is carried out using management functions, namely 1) Planning, Job Analysis, Recruitment, Job Orientation, 2) Workforce Development, 2) Work Performance Assessment 3) Providing Compensation, 4) Workforce Maintenance 5) Termination of the function of having which is similar to the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 18 of 2019 concerning General Guidelines for Assistance to Village Communities, namely recruitment, increasing performance capacity, certification of village assistants, and performance evaluation.